Early Work on Land and Maori Law - Boast, Richard (Victoria University of Wellington Law Review, 1999)
This article introduces the final section of this issue of the Victoria University of Wellington Law Review, which contrasts the work of Professor Richard Maclaurin and Judge Acheson.